PENGARUH LATIHAN DRIBBLE BACK AND FORTH BETWEEN THREE CONES TERHADAP KOORDINASI DRIBBLE PADA PEMAIN SSB YAPORA PRATAMA U-15. - Gilang Ramadhan; Drs. Slamet '; Drs. Yuherdi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research was conduted tp determine effect of exercise dribble back and forth between three cones to dribble coordination on SSB Yapora Pratama U-15 players, that while dribbling can be done well and correctly. The method is experimental research metod and population is SSB Yapora Pratama U-15 with a sample 20 students. Sampling technique that the overall population. Instruments used in a research is dribble back and forth between three cones, aim to measure the coordination of dribble players, then soccer dribble test as a measurement. Afterwards, the data proccesed by statistics to examine the normality by using lilifors test at significance level 0,05α. Hypothesis is believed to exercise a significant influence dribble back and forth between three cones to dribble coordination on SSB Yapora Pratama U-15. Data from pretest soccer dribble test as colculated produce Lcount 0,1898 < Ltable 0,19. IT means Lcount < Ltable. Concluded the data pretest soccer dribble test were normally distributed. Post test data soccer dribble test produce Lcount 0,1880 < Ltable 0,19. Concluded the data post test soccer dribble test were normally distributed. By test analysis produce Tcount 8,1 and Ttable 1,725 that Tcount > Ttable it can be concluded Ha accepted.Therefore, there was significant influence dribble back and forth between three cones to dribble coordination dribble on SSB Yapora Pratama U-15 players.Keyword: Dribble Back And Forth Between Three Cones, Coordination Dribble, SSB Yapora Pratama